Temperature-resistant high-strength and high-toughness well cementation cement system and preparation method thereof

By using specific combinations of materials in cementing cement, the problems of cement stone decline and insufficient toughness in high temperature environments are solved, and the effects of high compressive strength and toughness are achieved, and environmental protection and cost advantages are provided.

CN119638323AActive Publication Date: 2025-03-18JIAHUA SPECIAL CEMENT
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411876624.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing cement cement has a declining strength and insufficient toughness in high temperature environments, making it difficult to meet the exploration and development needs of deep oil and gas resources.

Method used

The combination of low-temperature silicate cement, granite waste, strength modifiers Type I and Type II, toughness modifiers, high-temperature stabilizers and dispersants is used to improve the high-temperature compressive strength and toughness of cement stone by reducing the calcium-silicon ratio, controlling the hydration rate, introducing activated aluminum ions and forming temperature-resistant aluminosilicon minerals.

Benefits of technology

It achieves high compressive strength and toughness of cement stone in high temperature environments, avoids strength decline, and reduces the use of silica sand, which has the advantages of green and environmental protection and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197048590000071
    Figure BDA0005197048590000071
  • Figure BDA0005197048590000081
    Figure BDA0005197048590000081
  • Figure BDA0005197048590000091
    Figure BDA0005197048590000091
Patent Text Reader

Abstract

The invention discloses a temperature-resistant, high-strength and high-toughness well cementation cement system and a preparation method thereof. The temperature-resistant, high-strength and high-toughness well cementation cement system comprises the following components in percentage by weight: 41-56wt% of low-heat Portland cement; 5 to 10 wt% of granite waste; 12-16 wt% of a strength modifier type I; 22-24 wt% of a strength modifier type II; 2-4 wt% of a toughness modifier; 2-3 wt% of a high-temperature stabilizer; and 1-2 wt% of a dispersant. The temperature-resistant high-strength and high-toughness well cementation cement system has the characteristics of high high-temperature strength, no recession, high toughness, low permeability, good channeling resistance, excellent engineering performance and the like; in addition, a large amount of solid waste is adopted, environmental pressure is reduced, and the method is environment-friendly and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementing materials for oil and gas field development, and in particular to a temperature-resistant high-strength and high-toughness cementing cement system and a preparation method thereof. Background Art

[0002] With the decline of the development potential of shallow oil and gas reservoirs, the development of oil and gas resources has gradually developed towards deep formations, unconventional oil and gas, and offshore oil and gas. The formation environment has become more complex and the difficulty of mining has increased. As the depth of the well increases, the temperature and pressure at the bottom of the well will continue to increase, which also puts higher requirements on cementing cement. Cementing cement is a brittle material. Under the influence of complex conditions such as temperature, pressure, drilling, injection and production, it is easy to produce micro cracks and micro annuli, which seriously affects the production capacity, production life and safety of oil and gas wells.

[0003] Application No. 202210203763.0 discloses a long-term high-temperature resistant, toughened cementing sand-added cement composite material and preparation method, wherein the solid components include cement, alumina, ultrafine high-purity silica sand, suspending agent and toughening material according to weight fraction; the toughening material includes latex fiber toughening agent and nano-graphene sheet. The liquid component is composed of water, nano-iron oxide and oil well cement admixture according to weight fraction. The invention compounds alumina, silica sand, toughening material and nano-iron oxide colloidal solution in a certain proportion, supplemented with a specific proportion of liquid components, to obtain a new high-temperature resistant cementing system that can be used in ultra-high temperature environments.

[0004] Application No. 202110219984.2 discloses a high-temperature resistant and elastic cement slurry system for shale oil and gas wells. The cement slurry system contains the following components in parts by weight: 100 parts of cement, 2 to 5 parts of toughening materials, 4 to 10 parts of elastic materials, 3 to 20 parts of reinforcing materials, 10 to 45 parts of high-temperature strength stabilizers, 0 to 120 parts of density regulators, 0.5 to 1 parts of dispersants, 2 to 4 parts of retarders, 3 to 7 parts of fluid loss reducers, and 0.1 to 1 parts of defoaming agents.

[0005] Application No. 201710512058.8 discloses a high temperature resistant cement slurry system for ultra-deep wells. The cement slurry system includes the following components in parts by weight: 100 parts of cement, 6-18 parts of high temperature fluid loss reducer, 25-40 parts of silica sand, 6-15 parts of high temperature retarder, 3-5 parts of high temperature stabilizer, and 0.4-2 parts of dispersant. The high temperature fluid loss reducer adopts a copolymer fluid loss reducer with a maximum temperature resistance of 180°C-230°C, and the high temperature retarder adopts a retarder with a maximum temperature resistance of 180°C-230°C.

[0006] Application No. 202110815046.9 discloses a high temperature resistant cementing cement system and a preparation method thereof. The cement system consists of a solid component and a liquid component, and the weight ratio of the solid component to the liquid component is 1:(0.2-0.9), wherein the solid component contains 25-85 weight % of cement, 4-60 weight % of silica sand and 4-60 weight % of fly ash, and the weight ratio of the silica sand to the fly ash is (0.0714-14):1; the liquid component contains water and additives.

[0007] In the above-mentioned prior art, although certain progress has been made in the compressive strength decay and toughening of cement slurry systems, as the well temperature gradually increases, the existing cement slurry systems can no longer meet the requirements of cementing construction under ultra-high temperature environments. Therefore, it is urgent to develop a temperature-resistant, high-strength and tough cementing system to provide assistance for the exploration and development of deep oil and gas resources in my country. Summary of the invention

[0008] In order to overcome the defects and shortcomings of the above-mentioned prior art, the present invention provides a temperature-resistant high-strength and high-toughness cementing cement system and a preparation method thereof, which solves the problems of strength decay and insufficient toughness of cement stone under high temperature conditions.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] In one aspect, a high-strength and high-toughness cementing cement system is provided, comprising the following raw materials in weight percentage:

[0011] Low heat Portland cement: 41-56wt%;

[0012] Granite waste: 5-10wt%;

[0013] Strength modifier type I: 12-16wt%;

[0014] Strength modifier type II: 22-24wt%;

[0015] Toughness modifier: 2-4wt%;

[0016] High temperature stabilizer: 2-3wt%;

[0017] Dispersant: 1~2wt%.

[0018] Furthermore, the SiO 2 Content ≥72wt%, Al 2 O 3 Content ≥12wt%, powder particle size is 325 mesh.

[0019] Furthermore, the strength modifier type I is a mixture of waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of (1-2):(1-2):1.

[0020] Furthermore, the SiO 2 The content is ≥75wt%, and the powder particle size is 800 mesh; the SiO 2 Content ≥70wt%Al 2 O 3 The content is ≥10wt%, and the powder particle size is 325 mesh; the SiO 2 Content ≥99wt%, powder particle size is 325 mesh.

[0021] The waste glass powder, fused quartz sand and tungsten tailings powder used in the strength modifier type I of the present invention are mainly composed of crystalline or amorphous silicon dioxide, and the granite waste and strength modifier type II mainly contain active silicon dioxide and aluminum oxide. Under the joint action, on the one hand, the calcium-silicon ratio of the cement system is reduced, and the use of silica sand is greatly reduced by replacing silica sand with solid waste, which is green and environmentally friendly; on the other hand, the hydration rate is controlled by different crystal forms of silica, thereby regulating the generation of high-temperature hydration products, and active aluminum ions can be introduced under the dissociation effect of the strength modifier type II to promote the generation of temperature-resistant aluminosilicate minerals, thereby improving the strength and temperature resistance of the system.

[0022] Furthermore, the strength modifier type II is prepared by mixing strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2, and the preparation method is as follows:

[0023] S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A;

[0024] S12, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A;

[0025] S13, the powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a strength modifier type II.

[0026] Furthermore, the strength stabilizing material A is formed by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1;

[0027] Preferably, the SiO 2 Content ≥ 85wt%, the waste siliceous shale is crushed and ground into powder, and the powder particle size is 600 mesh;

[0028] Preferably, the SiO 2Content ≥ 65wt%, Al 2 O 3 Content ≥ 15wt%, biomass slag is dried and ground into powder, and the powder particle size is 600 mesh;

[0029] Preferably, the SiO 2 Content ≥55wt%, Al 2 O 3 Content ≥ 20wt%, carbon content ≥ 10wt%, particle size 375 mesh;

[0030] The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2;

[0031] Preferably, the SiO 2 Content ≥47wt%, Al 2 O 3 Content ≥40wt%;

[0032] Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh;

[0033] Preferably, the SiO 2 Content ≥40wt%, MgO content ≥50wt%, powder particle size <600 mesh;

[0034] The crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards;

[0035] More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.

[0036] The strength modifier type II of the present invention adopts SiO 2 and Al 2 O 3 The solid waste ensures the calcium-silicon ratio and high-temperature strength of the cement slurry system, greatly reducing the use of silica sand. It can also improve the high-temperature compressive strength of cement paste and ensure that the compressive strength of cement paste does not decline in high-temperature environments.

[0037] The specific principle is as follows: (1) the strength stabilizing material B of the present invention and the strength stabilizing material A jointly reduce the calcium-silicon ratio of the cement system, and can also form Mg(OH) during the high-temperature hydration process of cement. 2, making cement paste have a certain degree of expansion; in addition, the filling and heterogeneous nucleation effect of nano-clay can refine the pore structure and reduce the porosity. The synergistic effect with the excellent temperature resistance of forsterite powder can greatly reduce the permeability of cement paste, strengthen the density and interface bonding ability of cement paste, and thus improve the anti-channeling ability and mechanical properties of cement paste. (2) Crystal inducing materials can act as seed materials in the cement hydration process to induce the cement hydration products to quickly crystallize at high temperatures to form more calcium asphaltite and tobermorite, thereby improving the high temperature resistance of cement paste and avoiding the decline of cement paste strength. (3) Taking advantage of the porous and large specific surface area characteristics of strength stabilizing material A, the crystal inducing material is loaded inside and on the surface of the pores of strength stabilizing material A. When the cement hydration products react with the active ions such as silicon and aluminum released by strength stabilizing materials A and strength stabilizing materials B, the presence of the crystal inducing material not only greatly accelerates the formation of calcium asphaltite and tobermorite, but also induces the formation of aluminosilicate minerals and aluminum substitutes, further enhancing the high temperature resistance of cement paste and avoiding the decline of strength. In addition, the small amount of carbon powder present in the strength-stabilizing material A can not only work together with the strength-stabilizing material B to fill the pores, but also provide crystallization points for the hydration products and promote hydration.

[0038] Furthermore, the toughness modifier is prepared by uniformly mixing sillimanite powder, expanded graphite and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

[0039] Furthermore, the purity of the sillimanite powder is greater than 99wt%, and the powder particle size is 325 mesh; the particle size of the expanded graphite is 80 mesh; the purity of the phenyl silicone rubber powder is greater than 99wt%, and the powder particle size is 325 mesh.

[0040] Furthermore, the high temperature stabilizer is a mixture of clay and laponite; the dispersant is an aldehyde-ketone condensate;

[0041] Preferably, the clay is one or both of chlorite and allophane.

[0042] On the other hand, a method for preparing a heat-resistant, high-strength and toughness cementing cement system is provided, wherein various masses of low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant are evenly mixed to obtain a heat-resistant, high-strength and toughness cementing cement system.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The heat-resistant and high-strength cementing cement system of the present invention has the characteristics of high high-temperature strength without decay, high toughness, low permeability, good anti-channeling property, excellent engineering performance, etc. In addition, a large amount of solid waste is used, which reduces environmental pressure, is green and environmentally friendly, and has low cost.

[0045] 2. The present invention improves the high temperature resistance of cement paste by using strength modifier type I and strength modifier type II in combination. The waste glass powder, fused quartz sand and tungsten tailings powder used in strength modifier type I are mainly crystalline or amorphous silicon dioxide, and the main components of strength modifier type II also include active silicon dioxide and alumina. Under the joint action of the two, on the one hand, the calcium-silicon ratio of the cement system is reduced; on the other hand, the hydration rate is controlled by different crystal forms of silicon dioxide, thereby regulating the generation of high-temperature hydration products. Active aluminum ions can also be introduced under the action of strength modifier type II, which can promote the generation of temperature-resistant aluminosilicate minerals and improve the strength and temperature resistance of the system.

[0046] 3. The toughness modifier of the present invention has excellent high temperature resistance. It combines inorganic fibrous materials (sillimanite powder), rubber elastic particles (phenyl silicone rubber powder) and flexible particles (expanded graphite) and increases not only the specific surface area and roughness of the toughness modifier through surface modification, but also the polar groups on the surface of the toughness modifier. This enhances the compatibility of the toughness modifier with cement stone, and the cement hydration products can adhere to the surface of the toughness modifier, so that the interfacial bonding strength in the interface transition zone is enhanced, thereby improving the mechanical properties of the cement stone. Under the synergy and action modification of each component, not only the elastic toughness and impact resistance of the cement stone are enhanced, but also the compressive strength of the cement stone is improved. In addition, the strength modifier type II mesocrystalline inducing material has certain inorganic fibers, which can work together with the toughness modifier to further improve the elastic toughness and impact resistance of the cement stone. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] In the following examples, low heat silicate cement is provided by Jiahua Special Cement Co., Ltd., high temperature retarder is diethylenetriamine penta methylenephosphonic acid organic acid, and high temperature fluid loss reducer is 2-acrylamide-2-methylpropanesulfonic acid polymer. Unless otherwise specified in the examples, all percentages are weight percentages.

[0049] Example 1

[0050] As a preferred embodiment of the present invention, a temperature-resistant high-strength and toughness cementing cement system of this embodiment has specific components as shown in Table 1 below:

[0051] Table 1

[0052] raw material Weight ratio (%) Low heat silicate cement 41 Granite waste 10 Strength Modifier Type I 16 Strength Modifier Type II 24 Toughness modifier 4 High temperature stabilizer 3 Dispersants 2

[0053] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.

[0054] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.

[0055] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

[0056] According to Table 1, various masses of low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant were mixed uniformly to obtain a temperature-resistant high-strength and toughness cementing cement system 1#.

[0057] Example 2

[0058] As a preferred embodiment of the present invention, a temperature-resistant high-strength and toughness cementing cement system of this embodiment has specific components as shown in Table 2 below:

[0059] Table 2

[0060] raw material Weight ratio (%) Low heat silicate cement 48 Granite waste 7 Strength Modifier Type I 14 Strength Modifier Type IⅡ 23 Toughness modifier 3 High temperature stabilizer 3 Dispersants 2

[0061] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.

[0062] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.

[0063] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

[0064] According to Table 2, various masses of low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant were mixed evenly to obtain a temperature-resistant high-strength and toughness cementing cement system 2#.

[0065] Example 3

[0066] As a preferred embodiment of the present invention, a temperature-resistant high-strength and toughness cementing cement system of this embodiment has specific components as shown in Table 3 below:

[0067] Table 3

[0068]

[0069]

[0070] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.

[0071] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.

[0072] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

[0073] According to Table 3, various masses of low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant were mixed uniformly to obtain a temperature-resistant high-strength and toughness cementing cement system 3#.

[0074] Example 4

[0075] As a preferred embodiment of the present invention, a temperature-resistant high-strength and toughness cementing cement system of this embodiment has specific components as shown in Table 4 below:

[0076] Table 4

[0077] raw material Weight ratio (%) Low heat silicate cement 56 Granite waste 5 Strength Modifier Type I 12 Strength Modifier Type II 22 Toughness modifier 2 High temperature stabilizer 2 Dispersants 1

[0078] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of 1:2:1.

[0079] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.

[0080] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

[0081] According to Table 4, various masses of low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant were mixed uniformly to obtain a temperature-resistant high-strength and toughness cementing cement system 4#.

[0082] Comparative Example 1

[0083] This comparative example is conventional high-temperature cementing cement, and its specific components are 57 wt% of G-grade oil well cement, 40 wt% of silica sand, 2 wt% of high-temperature stabilizer, 1 wt% of dispersant, and a water-cement ratio of 0.44.

[0084] Comparative Example 2

[0085] This comparative example is the same as Example 1, except that the strength modifier type I does not contain fused quartz sand, and a cementing cement system 1* is obtained.

[0086] Comparative Example 3

[0087] This comparative example is the same as Example 1, except that the strength modifier type II does not contain a crystal inducing material, and a cementing cement system 2* is obtained.

[0088] Comparative Example 4

[0089] This comparative example is the same as Example 1, except that the toughness modifier does not contain phenyl silicone rubber powder, and a cementing cement system 3* is obtained.

[0090] Test Case

[0091] The cement slurry was prepared according to GB / T19139 standard, with a liquid-to-solid ratio of 0.44. The engineering performance of the cement slurry prepared by the heat-resistant high-strength and toughness cementing cement system obtained in Example 1 was evaluated, and a 210°C test was performed according to the following formula. The formula composition and test results are shown in Table 5.

[0092] Table 5

[0093]

[0094]

[0095] According to the data in Table 5, it can be found that the water loss of the cement slurry prepared by the heat-resistant high-strength cementing system of the present invention is less than 50 ml, and the upper and lower density difference is less than 0.04 g / cm 3 The system has good compatibility with admixtures (high-temperature retarder and high-temperature fluid loss reducer), the thickening time is adjustable, the anti-channeling coefficient SPN value is less than 1, the anti-channeling performance is good, it meets the construction requirements in high-temperature environment, and is conducive to improving the safety of high-temperature cementing operations.

[0096] Cement slurry was prepared according to GB / T19139 standard, with a liquid-to-solid ratio of 0.44. The cement slurry prepared by the cement system obtained in the above Examples 1 to 4 and the comparative examples was poured into a copper mold and then placed in a high-temperature curing kettle for curing to obtain cement stone. The curing temperature was 260°C, and the curing period was 2d, 7d, and 28d. The compressive strength and permeability of the cement stone were tested, and the test results are shown in Table 6. The cement stone after curing was cored and then subjected to a triaxial mechanical property test. The test results are shown in Table 7.

[0097] Table 6

[0098]

[0099] From the data in Table 6, it can be seen that compared with Comparative Example 1, the cement slurry prepared by the cement system of Examples 1 to 4 has a compressive strength greater than 40 MPa after curing for a certain period of time at 260°C, and does not show any decline; the permeability is lower than 0.20 mD, indicating that the internal structure has a high density. Comparative Examples 2 to 4 show that the present invention has the effect of improving the compressive strength and high temperature resistance of cement stone, and the components have a synergistic effect, and the lack of any one of them cannot achieve the expected effect of the present application.

[0100] Table 7

[0101]

[0102] From the measured data in Table 7, it can be seen that the present invention can effectively reduce the elastic modulus of cement paste in a high temperature environment, indicating that it has good toughness and can effectively solve the problem of insufficient toughness of cement paste in a high temperature environment. In addition, compared with the results of Comparative Examples 2 to 4, the components in the present invention have a synergistic effect, and the lack of any one of them cannot achieve the expected effect of the present invention.

[0103] In summary, the present invention can improve the density and strength of cement paste, effectively inhibit the decline of cement paste strength, reduce the elastic modulus of cement paste under high temperature environment, improve the high temperature toughness of cement paste, and the components have a synergistic effect. Without any one of them, the expected effect of the present invention cannot be achieved. Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical scheme of the present invention, but not to limit it, and certainly not to limit the patent scope of the present invention; although the present invention is described in detail with reference to the above embodiments, ordinary technicians in this field should understand that it can still modify the technical schemes recorded in the above embodiments, or replace part or all of the technical features therein; and these modifications or replacements do not make the essence of the corresponding technical schemes deviate from the scope of the technical schemes of the embodiments of the present invention; that is, any changes or polishing made on the main design ideas and spirit of the present invention without substantial meaning, the technical problems solved by them are still consistent with the present invention, and should be included in the protection scope of the present invention; in addition, the direct or indirect application of the technical scheme of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A temperature-resistant high-strength and high-toughness cementing cement system and a preparation method thereof, characterized in that: The following raw materials are included in weight percentage: Low heat Portland cement: 41-56wt%; Granite waste: 5-10wt%; Strength modifier type I: 12-16wt%; Strength modifier type II: 22-24wt%; Toughness modifier: 2-4wt%; High temperature stabilizer: 2-3wt%; Dispersant: 1~2wt%.

2. A temperature-resistant and high-strength cementing system according to claim 1, characterized in that: The SiO2 content of the granite waste is ≥72wt%, the Al2O3 content is ≥12wt%, and the powder particle size is 325 meshes.

3. A temperature-resistant and high-strength cementing cement system according to claim 1, characterized in that: The strength modifier type I is prepared by mixing waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of (1-2):(1-2):

1.

4. A temperature-resistant and high-strength cementing system according to claim 3, characterized in that: The SiO2 content of the waste glass powder is ≥75wt%, and the powder particle size is 800 mesh; the SiO2 content of the tungsten tailings powder is ≥70wt%, the Al2O3 content is ≥10wt%, and the powder particle size is 325 mesh; the SiO2 content of the fused quartz sand is ≥99wt%, and the powder particle size is 325 mesh.

5. The temperature-resistant and high-strength cementing system according to claim 1, characterized in that: The strength modifier type II is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2, and the preparation method is as follows: S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A; S12, performing solid-liquid separation and drying on slurry A to obtain powder A; S13, the powder A and the strength stabilizing material B are mixed evenly by a pneumatic mixing device to obtain a strength modifier type II.

6. A temperature-resistant high-strength and high-toughness cementing system according to claim 5, characterized in that: The strength stabilizing material A is made by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1; Preferably, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form a powder with a particle size of 600 mesh; Preferably, the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 mesh; Preferably, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 mesh; The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2; Preferably, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%; Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh; Preferably, the forsterite powder has a SiO2 content of ≥40wt%, a MgO content of ≥50wt%, and a powder particle size of <600 mesh; The crystal inducing material is waste inorganic insulation material, preferably waste insulation bricks or waste insulation boards; More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.

7. The temperature-resistant high-strength and high-toughness cementing system according to claim 1, characterized in that: The toughness modifier is prepared by uniformly mixing sillimanite powder, expanded graphite and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.

8. The temperature-resistant high-strength and high-toughness cementing system according to claim 7, characterized in that: The purity of the sillimanite powder is greater than 99wt%, and the powder particle size is 325 mesh; the particle size of the expanded graphite is 80 mesh; the purity of the phenyl silicone rubber powder is greater than 99wt%, and the powder particle size is 325 mesh.

9. The temperature-resistant high-strength and high-toughness cementing system according to claim 1, characterized in that: The high temperature stabilizer is a mixture of clay and laponite; the dispersant is an aldehyde-ketone condensate; Preferably, the clay is one or both of chlorite and allophane.

10. The method for preparing a temperature-resistant high-strength and high-toughness cementing system according to any one of claims 1 to 9, characterized in that: Low-heat cement, granite waste, strength modifier type I, strength modifier type II, toughness modifier, high-temperature stabilizer and dispersant of various masses are uniformly mixed to obtain a temperature-resistant, high-strength and toughness cementing cement system.

Citation Information

Patent Citations

  • High-temperature-resistant cement paste system for ultradeep wells

    CN107162512A

  • High-temperature-resistant elastic and tough cement paste system for shale oil-gas well

    CN112830723A

  • High-temperature-resistant well cementation cement system and preparation method thereof

    CN113582605A

  • Long-term high-temperature-resistant toughened well-cementing sand-added cement composite material and preparation method thereof

    CN114477876A

  • Ultrahigh-temperature high-strength tough cement paste system

    CN112341067A